Projecting human pharmacokinetics of monoclonal antibodies from nonclinical data: comparative evaluation of prediction approaches in early drug development. (15th May 2015) - Wang, Jing; Iyer, Suhasini; Fielder, Paul J.; Davis, John D.; Deng, Rong
Abstract: Currently, more than 350 monoclonal antibodies (mAbs) and mAb derivatives are under development as therapeutics. The prediction of mAb pharmacokinetics (PK)/pharmacodynamics (PD) plays a key role in starting dose selection for first‐in‐human (FIH) studies. This article presents a brief overview of the biology and mechanisms of absorption, distribution, metabolism and excretion (ADME) for mAbs. In addition, a detailed review of mAb human PK/PD prediction from nonclinical data is provided, including allometry for mAbs with linear or nonlinear PK, species‐invariant time method, physiologically based PK (PBPK) modeling and target‐mediated drug disposition (TMDD) model, bioavailability projection and immunogenicity impact on PK prediction. Finally, from an industry perspective a decision tree of mAb human PK projection is proposed to facilitate drug development. Copyright © 2015 John Wiley & Sons, Ltd.